2005
DOI: 10.1161/circulationaha.104.515106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Unloading During Left Ventricular Assist Device Support Increases Left Ventricular Collagen Cross-Linking and Myocardial Stiffness

Abstract: Background-Left ventricular assist devices (LVADs) induce reverse remodeling of the failing heart except for the extracellular matrix, which exhibits additional pathophysiological changes, although their mechanisms and functional consequences are unknown. Methods and Results-Hearts were obtained at transplant from patients with idiopathic dilated cardiomyopathy (DCM) not requiring LVAD support (nϭ30), patients requiring LVAD support (nϭ16; LVAD duration, 145Ϯ33 days), and 5 nonfailing hearts. Left (LV) and rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 63 publications
11
134
1
3
Order By: Relevance
“…The differences in this association between the BM and collagen fibers may be due to alterations of the BM but may also be caused by the changes in the ECM. 15,36,37 With IHC, we showed a significant reduction of type IV collagen immunoreactivity in the BM after LVAD support. However, laminin was still present in the BM after unloading of the heart.…”
Section: Basement Membrane Degradation After Lvad Ah Bruggink Et Almentioning
confidence: 78%
See 1 more Smart Citation
“…The differences in this association between the BM and collagen fibers may be due to alterations of the BM but may also be caused by the changes in the ECM. 15,36,37 With IHC, we showed a significant reduction of type IV collagen immunoreactivity in the BM after LVAD support. However, laminin was still present in the BM after unloading of the heart.…”
Section: Basement Membrane Degradation After Lvad Ah Bruggink Et Almentioning
confidence: 78%
“…[35][36][37] In a previous study of our group, 15 we have shown that reverse remodeling of type I and III collagen in the ECM follows a biphasic pattern. Initially, an increase of type I and III collagen turnover takes place, which is paralleled by an increase of the ECM volume.…”
Section: Basement Membrane Degradation After Lvad Ah Bruggink Et Almentioning
confidence: 81%
“…54 Secondly, myocardial fibrosis (antecedent scarring or localized injury induced by cannula placement) increases the propensity for arrhythmias. 59 Use of angiotensin-converting enzyme inhibitors may reduce levels of fibrosis and collagen deposition. The third aspect is the electrophysiological adaptation to LVAD support.…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…The changes in ECM during this process of reverse remodeling resulted not only in a time-dependent change of type I and type III collagen protein (Goldsmith and Borg, 2002;Stamenkovic, 2003), but also in considerable changes in composition of the basal membrane. These included amongst others reduced collagen type IV content in the cardiomyocyte basal membrane, as a result of increased matrix metalloproteinase activity (Bruggink et al, 2007;Spinale, 2002;Li et al, 2001;Klotz et al, 2005). So, during LVAD support myocardial architecture and composition change at the level of both the cardiomyocytes and the ECM.…”
Section: Introductionmentioning
confidence: 99%